Study of The Lazy Nature of Physics Students Using The Quadratic Optimal Control Method - Dimas Kukuh Nur Rachim (Program Studi Pendidikan Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2020)
The lazy nature of learning is an obstacle in teaching and learning activities. The higher level of laziness will reduce the students learning achievement. This problem has motivated the author to make a mathematical model of student learning's lazy nature and analyze it. The lazy nature of learning is modeled to a discrete-time system with , denotes a state vector of the lazy nature, represents an input vector system in time, and denotes a coefficient matrix of and . The optimal quadratic control method is applied in the model to analyze the system's stability and give the interpretation of the model based on the graphics info obtained during the simulation process. The feedback controller is obtained as a result of optimizing the quadratic objective function. a feedback controller's existence makes the lazy nature of learning physics students decrease from time to time, and the system becomes stable.